Some Aspects of the Organization of "Corridors of Health" in the Historical Centers of the Cities of Uzbekistan - А. Zokirova L.; E., Matniyazov Z. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the main aspects of the organization of "health corridors" in the historical centers of the cities of Uzbekistan. The need for pedestrian walking in the urban environment is caused physiologically and psychologically. A person was formed in the natural environment, and walking, physical activity is necessary for him for full physical development. Socio-economic status and the level of social inequality of the urban population also have a significant impact on the spread of "health corridors" in the city, on people’s participation in active forms of leisure. The integration of “health corridors” is a process of synergizing the pedestrian framework and the fabric of the city.